The Greek Revolution of 1821 and Russian Policy in the Eastern Question - E. P. Kudryavtseva (Vestnik MGIMO-Universiteta, 2021)
The Greek Revolution 1821-1829 contributed to the beginning and development of the Eastern crisis of the 1820s, which led to the military confrontation in the Russian-Turkish relations in 1828-1829. The Russian government was forced to closely monitor the unfolding events in Greece, repeatedly expressing the Sublime Porte condemnation of her repression against the Greek population. During the crisis the Petersburg Cabinet has repeatedly attempted to settle the Greek-Turkish conflict diplomatically by means of a joint statement of the European powers addressing the Ottoman government. The agreements adopted at the St. Petersburg (1826) and London (1827) conferences of the powers were aimed at "pacifying" the Greek problem through the joint efforts of the European powers. Ineffective European actions resulted in the fact that Russian government was forced to radically change its policy on the Greek issue and declare its determination to take independent steps to resolve the Greek issue and start military operations against the Ottoman Empire.The Greek uprising of 1821 became the central event of the 1820s. in the Balkans. Standing in the same row with the revolutionary movements in European countries, the Greek revolution led to a change in the entire foreign policy doctrine of the Russian government. It was forced, despite the adherence of the Russian emperors to the principles of the Holy Alliance, not only to provide the rebel Greeks with material and moral support, but also to openly declare to the allies about the existing interests in the Balkans. Match of these interests with the demands for independence of the Greek movement leaders led to a more decisive steps taken by the Russian government in the Greek issue. The Russian Empire took path of an independent policy in the Eastern question, which contributed to the victory of the national interests of Greece.